(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
All over the world, there are currently contradictions in the development of material and moral qualities. In the process of development of world civilization under the influence of scientific and technological world ownership, human thinking becomes purposeful, rational, purely instrumental and unable to critically analyze the strategic goals of scientific and technological culture. The work of education and upbringing in the country is undoubtedly connected with the development of society, which poses important tasks.